Method of technical training of football players during pre-basic training - Matyas, V. V. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The question of technical training football players is considered. Revealed that the percentage of defects in the performance of technical elements of a good at football players of different ages. In the main experiment participated 44 players. The study used data from testing of technical training young players 10-11 years. It was revealed that the curricula of different authors (except the French) offer to study each technique separately in different sequences. The technique of technical training in the annual cycle during the pre-basic training, taking into account the sequence of techniques. Found that the ratio error decreased from 42 (90%) and 14 (58%). It is shown that in-depth training players 10-11 years are characterized by combining several techniques. A significant improvement in the technical readiness of young players.